2023
DOI: 10.3390/rs15215125
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the 2022 Extreme Drought Event over the Poyang Lake Basin Using Multiple Satellite Remote Sensing Observations and In Situ Data

Sulan Liu,
Yunlong Wu,
Guodong Xu
et al.

Abstract: With advancements in remote sensing technology and the increasing availability of remote sensing platforms, the capacity to monitor droughts using multiple satellite remote sensing observations has significantly improved. This enhanced capability facilitates a comprehensive understanding of drought conditions and early warnings for extreme drought events. In this study, multiple satellite datasets, including Gravity Recovery and Climate Experiment (GRACE), the Global Precipitation Measurement (GPM) precipitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 75 publications
1
1
0
Order By: Relevance
“…In China, the drought also lowered the water level of Poyang Lake, the largest freshwater lake in China, to its lowest level since 1955. The minimum area of Poyang Lake estimated by satellite data was 814 km 2 , which matched well with the observed drought characteristics [60]. In the recent research focused on drought assessment within the Changjiang River Basin, satellites equipped with altimeters were used [61,62].…”
Section: Discussionsupporting
confidence: 77%
“…In China, the drought also lowered the water level of Poyang Lake, the largest freshwater lake in China, to its lowest level since 1955. The minimum area of Poyang Lake estimated by satellite data was 814 km 2 , which matched well with the observed drought characteristics [60]. In the recent research focused on drought assessment within the Changjiang River Basin, satellites equipped with altimeters were used [61,62].…”
Section: Discussionsupporting
confidence: 77%
“…With research progress on regional land water storage changes, more studies have shown that the terrestrial water storage in a basin will produce significant changes under the dual impact of climate change and human activities [30], which cannot be ignored in the water balance equation of a closed basin. With the available data from the GRACE/GRACE-FO gravity satellite, changes in terrestrial water storage in large-scale watersheds can be calculated efficiently and accurately [31,32].…”
Section: Methods 231 Calculation Of Actual Et Adopt On Water Balance ...mentioning
confidence: 99%